Beyond buying: Extending the concept of acquisition in consumption - Bardhi, Fleura; Corciolani, Matteo; Dalli, Daniele; Maraj, Varala (Journal of the Academy of Marketing Science, 2025)
Abstract The consumption process constitutes a sequence of acquisition, use/consumption, and disposal. Over the last two decades, acquisition has transformed due to digitization and sharing economy innovations. Consumers obtain goods and services through several practices beyond buying, including renting, sharing, streaming, borrowing, and gifting. Access constitutes equal options to ownership, and non-market-mediated exchanges have become alternatives to market exchanges. While research has begun to study these practices, it remains fragmented, and we lack a unifying conceptual framework of acquisition. This gap risks marketers overlooking the acquisition phase, the essential first touchpoint in the customer journey. We develop a new conceptual acquisition framework organized by the levels of ownership transfer and market mediation. It distinguishes four acquisition modes: market-mediated ownership, market-mediated access, non-market-mediated ownership, and non-market-mediated access. We extend the acquisition concept beyond buying and market exchange, contributing to research on access, sharing, and customer journey, and we advance a future research agenda.